Peningkatan Hasil Belajar IPS Melalui Metode Round Club Siswa Kelas V SDN 1 Hendea - suarti suarti; Andi MUHAMMAD ALI; manan manan; musrianton musrianton (Universitas Negeri Makassar, 2022)
This study aims to improve student learning outcomes in social science subjects through the Round Club method in grade V Primary School 1 Hendea, South Buton Regency. This type of research is Classroom Action Research which includes the stages of Planning, Action, Observation and Reflection. The research activity was carried out in the 2020/2021 academic year in social science subjects with the sub-theme of national events in colonialism on the material factors that caused the Indonesian nation to colonize. the results of the research data analysis cycle I and cycle II it was found that there was an increase in student learning outcomes in the first cycle, the results obtained were 20 students scored 60% complete, 13 students scored below or 39% incomplete. While in the second cycle, 30 students obtained scores above 90% complete, 3 students scored below or 9.90% incomplete. it can be concluded that student learning outcomes can increase